Cinematic - Mosab Dwaikat (My University, 2024)
The Cinematic streaming platform is a revolutionary initiative designed to address the dynamic landscape of the entertainment industry in the Middle East. In recent years, digital technology has transformed content consumption, making streaming platforms the primary source for movies and TV shows. While this shift has been embraced globally, the Middle East has often been underserved, lacking platforms that cater specifically to its diverse cultural preferences. This graduation project presents the development and implementation of Cinematic. The project aims to bridge the gap in entertainment content availability, empower local content creators, and provide a tailored cinematic experience for the Middle Eastern audience. The platform places a strong emphasis on user-centric design, sustainable monetization models, and cultural relevance. The objectives encompass addressing content limitations, overcoming content creator hesitancy, and ensuring a seamless and cost-effective entertainment experience. The significance of this project lies in its potential to contribute to the cultural enrichment of the global entertainment landscape while fostering innovation and meeting the diverse needs of Middle Eastern users. The theoretical foundation is rooted in user-centric design principles and insights from economic theories and business models, ensuring the platform's alignment with evolving digital entertainment trends. Building upon successful initiatives in the streaming industry, the project leverages lessons learned from global and regional streaming services, as well as user-generated content platforms. The methodology encompasses a comprehensive approach to development, including tools, methods, and programming languages. React JS, Material UI, Node.js, Express.js, Stripe, and MongoDB form the technological backbone, ensuring efficiency, scalability, and a seamless user experience. The development process considers constraints such as content licensing challenges, technical infrastructure variations, and the need for effective user acquisition and retention strategies. The system features a user-friendly landing page, a secure login process, an intuitive registration page, a dynamic home screen, a robust search page, and an information panel for detailed content exploration. The play page serves as the heart of the streaming experience, while admin statistics, customer support, Stripe Dashboard, and a comprehensive Help Center enhance the overall platform functionality.